Public Feminisms (Lever Press, 2023)
The field of feminist studies grew from the U.S. women’s movements of the 1960s and 1970s and has continued to be deeply connected to ongoing movements for social justice. As educational institutions are increasingly seeing public scholarship and community engagement as relevant and fruitful complements to traditional academic work, feminist scholars have much to offer in demonstrating different ways to inform and interact with various communities. In Public Feminisms: From Academy to Community edited by Carrie N. Baker and Aviva Dove-Viebahn, a diverse range of feminist scholar-activists write about the dynamic and varied methods they use to reach beyond the traditional academic classroom and scholarly journals to share their work with the public.